Modelling of transition from upper to lower bainite in multi-component system. Issue 4 (4th March 2017) - Guo, L.; Roelofs, H.; Lembke, M.I.; Bhadeshia, H.K.D.H.
Abstract : A model for estimating the upper to lower bainite transition has been developed for the iron–carbon–manganese–chromium–silicon alloy system by comparing the time required to decarburise a supersaturated bainitic ferrite platelet and that needed for the start of cementite precipitation in the ferrite. The problem is treated as a competition between the decarburisation time and the kinetics of cementite precipitation. Lower bainite is induced when the latter process is faster. The time for forming a volume fraction of 0.01 of the equilibrium amount of cementite is taken as the precipitation start time. The model was calibrated using experimental data from the iron–carbon system, and verified with the iron–carbon–manganese–molybdenum system and an experimental steel currently being developed for high-strength applications.